Glycemic Control and Bone Turnover in Older Mexican Americans with Type 2 Diabetes - Nahid J. Rianon; Scott M. Smith; MinJae Lee; Hannah Pervin; Paul Musgrave; Gordon P. Watt; Shahla Nader; Sundeep Khosla; Catherine G. Ambrose; Joseph B. McCormick; Susan P. Fisher-Hoch (Journal of Osteoporosis)
Altered bone quality, caused by underlying metabolic changes of type 2 diabetes (T2D), has been hypothesized to cause altered bone strength and turnover leading to increased fracture risk in T2D patients. Current understanding about changes in bone turnover markers in T2D patients is mainly based on studies focused on Caucasian men and women. However, Hispanic populations have the highest prevalence of both T2D and osteoporosis in the US. We investigated associations of glycemic control (in terms of glycated hemoglobin [HbA1c]) and bone turnover rate in 69 older (≥50 years) Mexican American Cameron County Hispanic Cohort (CCHC) participants with T2D. Multivariable analyses were conducted to assess the associations between HbA1c (%), serum osteocalcin (OC), and serum sclerostin. In agreement with published reports from other racial/ethnic populations, our study found that lower bone turnover (indicated by lower serum OC) occurred in Mexican American men with T2D who had poorer glycemic control. For the women in our study, we found no significant association between glycemic control and OC. In contrast, HbA1c was positively associated with sclerostin for women, with near significance (p=0.07), while no association was found in men. We recommend screening Mexican American individuals with T2D, specifically those with poor glycemic control, for bone loss and fracture risk.